Great Expectations: Plans and Predictions for New Horizons Encounter With Kuiper Belt Object 2014 MU69 ("Ultima Thule"). Issue 16 (24th August 2018) - Moore, Jeffrey M.; McKinnon, William B.; Cruikshank, Dale P.; Gladstone, G. Randall; Spencer, John R.; Stern, S. Alan; Weaver, Harold A.; Singer, Kelsi N.; Showalter, Mark R.; Grundy, William M.; Beyer, Ross A.; White, Oliver L.; et al.
Abstract: The New Horizons encounter with the cold classical Kuiper Belt object 2014 MU69 (informally named "Ultima Thule, " hereafter Ultima) on 1 January 2019 will be the first time a spacecraft has ever closely observed one of the free‐orbiting small denizens of the Kuiper Belt. Related to but not thought to have formed in the same region of the solar system as the comets that been explored so far, it will also be the most distant, and most primitive body yet visited by spacecraft. In this letter we begin with a brief overview of cold classical Kuiper Belt objects, of which Ultima is a prime example. We give a short preview of our encounter plans. We note what is currently known about Ultima from Earth‐based observations. We then review our expectations and capabilities to evaluate Ultima's composition, surface geology, structure, near space environment, small moons, rings, and the search for activity. Plain Language Summary: The letter discusses the current state‐of‐knowledge for the cold classical Kuiper Belt object 2014 MU69, the target of a close encounter by NASA's New Horizon spacecraft on 1 January 2019. We also review our encounter plans and make broad speculative predictions as to might be revealed by our observations. New Horizons will fly to within 3, 500 km of 2014 MU69 (informally named "Ultima Thule"), acquiring images with pixel scale resolutions significantly better than 100 m/pixel). We plan to obtain topography derived from stereo imaging and body shape. Our spectroscopic observations potentially could detect H2 O, CH4, N2, CH3 OH, and NH3, depending on their brightness and abundance on the surface. We will also search for evidence of outgassing, small moons, and rings. This exploration will transform Kuiper Belt and Kuiper Belt object science from a purely astronomical regime, to a geological and geophysical regime, which radically changed paradigms when the same happened to asteroids and comets in past decades. Key Points: New Horizons will fly to within 3, 500 km of 2014 MU69, acquiring images with pixel scale resolutions significantly better than 100 m/pixel Our spectroscopic observations potentially could detect H2 O, CH4, N2, CH3 OH, and NH3, depending on their brightness and abundance We will evaluate Ultima's composition, surface geology, structure, near space environment, and the search for small moons, rings, and activity